Günter Grass und die Berliner Republik Eine biografische Fallstudie über die kommunikative Macht von Intellektuellen - Stausberg, Friederike Laura (De Gruyter, 2023)
Günter Grass has primarily been perceived by research and the public as an author. But he was also an influential political actor. His political work was not just limited to the Brandt era but also helped to define the Berlin Republic. By harnessing his communicative power, he shaped public discourses as an intellectual and advised top politicians, as unpublished sources and background conversations show.